Faktor Penentu Cost Of Equity di Industri Properti dan Real Estate - Suryanto Suryanto; Sarah Maulidina (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2019)
This study aims to determine the factors that determine the cost of equity in the property and real estate industry. The research method used in this research is descriptive and verification. Sources of data obtained from secondary data published. The data used is panel data obtained from 14 property and real estate companies for a period of 3 years. The analysis technique uses multiple regression and the coefficient of determination. To test the factors that affect the cost of equity using the t test and F test. The results of the study state that the factors that affect the cost of equity are firm siza and disclosure, while asymmetric information is not a factor affecting the cost of equity. However, if carried out simultaneously asymmetric information, firm siza and disclosure are factors that affect the cost of equity.